Shape characteristics and aesthetics in postmodern sculptures (Journal of the College of Basic Education, 2022)
The current research is interested in studying the formal and aesthetic characteristics of postmodern stereoscopic sculptures (Pop Art as a model), which embodied many themes and different materials.Thus, the research problem in the first chapter was determined by the following question: What is the extent to which pop artists have come to use raw materials from daily life to represent popular culture? What is the importance of the sculptural achievement and its formal and aesthetic specificity? And did the changes witnessed by European society make it imperative for the artist to change the shape in relation to the structure of the sculptural achievement?The importance of the research is evident in the possibility of considering the current study as a scientific addition in terms of forming an important benefit for specialists studying in this field, as well as the possibility of viewing the development reached by postmodern sculpture, in addition to the need for the library for such a study.